(untitled) (Acta Entomologica Serbica, 2010)
following species: Loxostege sticticalis, Ostrinia nubilalis, Autographa gamma, Helicoverpa armigera, Spodoptera exigua, Lacanobia oleracea, Mamestra brassicae, Agrotis ipsilon, A. exclamationis, A. segetum and Hyphantria cunea. Frequencies are given and compared with averages for the period 1980–2004. The year 2010 was very humid, because temperature conditions were similar to average ones and precipitation was much higher than the long-term average. The hydrophilic species L. oleracea and A. ipsilon showed a frequency much above average; A. gamma and M. brassicae were less frequent than on average, but still had an impact on agriculture production in 2010 in Vojvodina. Usual conditions in July and August favored O. nubilalis and H. armigera, so their impact on agriculture production was also significant. Forecasts suggest increased frequency for the first generation in 2011 of the species L. oleracea, A. exclamationis and H. cunea. A negative trend is predicted for O. nubilalis, but it can still cause significant damage due to the large number of recorded moths. A. segetum is expected to show an increase in some places and a decrease in others, but its frequency was too small to expect widespread damage in 2011. For the species L. sticticalis, A. gamma, H. armigera, S. exigua, M. brassicae and A. ipsilon, long-term forecasts are not presented because of their migratory nature.